2013
DOI: 10.1002/aenm.201300998
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes in Li2MnO3 Cathode Material for Li‐Ion Batteries

Abstract: Structural changes in Li 2 MnO 3 cathode material for rechargeable Li-ion batteries were investigated during the 1 st and 33 rd cycles by X-ray absorption spectroscopy. It is found that both the participation of oxygen anions in redox processes and Li + -H + exchange play an important role in the electrochemistry of Li 2 MnO 3 . During activation, oxygen removal from the material along with Li gives rise to the formation of a layered MnO 2 -type structure, while the presence of protons in the interslab region,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
193
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(213 citation statements)
references
References 56 publications
17
193
3
Order By: Relevance
“…[ 12 ] We note that in the Li x Mn 4/3 O 4 environments, Mn remains fully coordinated by O, in agreement with the work in ref. [ 7 ] ; however, O is under-coordinated, surrounded on average by 2, instead of 3 Mn.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…[ 12 ] We note that in the Li x Mn 4/3 O 4 environments, Mn remains fully coordinated by O, in agreement with the work in ref. [ 7 ] ; however, O is under-coordinated, surrounded on average by 2, instead of 3 Mn.…”
Section: Discussionsupporting
confidence: 84%
“…[ 34 ] These structural transformations are sometimes attributed to the insertion of protons, arising from electrolyte decomposition, into cycled Li 2 MnO 3 . [ 11,12,15 ] However, a recent study combining solid state nuclear magnetic resonance and X-ray absorption spectroscopies with fi rst principles calculations has indicated that proton insertion is not a signifi cant contributor. [ 16 ] An alternative mechanism invokes the loss of oxygen from the oxide as the dominant process governing structural transformations.…”
Section: Discussionmentioning
confidence: 97%
“…[ 18,21 ] This MnO 2 component can intercalate Li + in the following discharge. According to Rana et al, [ 19,20 ] this MnO 2 -type structure changes to an Li 2 MnO 3 -type structure when Li + are inserted into it during discharge. Moreover, it is reported that the Mn ions remain in its tetravalent oxidation state throughout the whole cycle.…”
Section: Introductionmentioning
confidence: 97%
“…This secondary mechanism becomes more significant at higher temperature. [12][13][14] Despite the promise of lithium rich TM oxides to deliver very high capacities, one significant limitation remains the large voltage and capacity fade observed upon extended electrochemical cycling. 15,16 A number of studies have attempted to link structural changes in lithium-rich TM oxides with electrochemical stability and cycling behavior.…”
mentioning
confidence: 99%